2020
DOI: 10.1016/j.heliyon.2019.e03117
|View full text |Cite
|
Sign up to set email alerts
|

Chemically reactive bioconvection flow of tangent hyperbolic nanoliquid with gyrotactic microorganisms and nonlinear thermal radiation

Abstract: On the account of motivating fabrication of bioconvection phenomenon in various engineering and industrial systems, an attention has been devoted by researchers in current decade. Therefore, this theoretical investigation deals with the utilization of bioconvection phenomenon in flow of tangent hyperbolic nanofluid over an accelerated moving surface. It is assumed that the flow is generated due to periodically motion of the sheet. The energy equation is modified by entertaining the nonlinear thermal radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Nanofluids have the tonic role when used with microorganisms to provide useful products for life and to eradicate the serious environmental issues. Al-Khaled et al 2 studied theoretically the application of bioconvection phenomena in periodically flow of tangent hyperbolic nanofluid over an accelerated moving surface with nonlinear thermal radiation, chemical reaction, thermophoresis and Brownian motion. Khan et al 3 used convective Nield boundary conditions to investigate the rheology of couple stress nanofluid with activation energy, porous media, thermal radiation, gyrotactic microorganisms employing Buongiorno nanofluid model, in addition to, second-order velocity slip (Wu's slip).…”
mentioning
confidence: 99%
“…Nanofluids have the tonic role when used with microorganisms to provide useful products for life and to eradicate the serious environmental issues. Al-Khaled et al 2 studied theoretically the application of bioconvection phenomena in periodically flow of tangent hyperbolic nanofluid over an accelerated moving surface with nonlinear thermal radiation, chemical reaction, thermophoresis and Brownian motion. Khan et al 3 used convective Nield boundary conditions to investigate the rheology of couple stress nanofluid with activation energy, porous media, thermal radiation, gyrotactic microorganisms employing Buongiorno nanofluid model, in addition to, second-order velocity slip (Wu's slip).…”
mentioning
confidence: 99%
“…Makinde and Animasaun 60 illustrated the radiative bioconvective nanoliquid flow over a paraboloid surface with chemical reaction. The same features for a tangent hyperbolic nanofluid over the oscillating surface were communicated by Al‐Khaled et al 61 Impact of buoyancy force on the chemically reactive gyrotactic bioconvective nanoliquid thin‐film flow was reported by Zuhra et al 62 Effect of higher‐order chemical reaction on Prandtl nanoliquid was addressed by Eid et al 63 They found that frictional effect becomes high for the magnetic field. More parallel studies are found in the following References [64–68].…”
Section: Introductionmentioning
confidence: 55%
“…Al-Khaled et al [29] deliberated the bioconvection flow of tangential hyperbolic nanofluids in the presence of chemical reaction, motile microorganisms, and thermal radiation. Shukla et al [30] considered the no similar bioconvective nanofluid flow pat an elongating sheet with nonlinear thermal radiation and inlined magnetic field effects for the entropy minimization analysis by employing HAM (Homotopy Analysis Method).…”
Section: Background Informationmentioning
confidence: 99%